Willingness of Local Tourists to pay for conservation of tourism spots in the Damai Sistrict Sarawak - Alias, Radam; Shazali, Abu Mansor; Abas, Said; Afizah, Merican (ASEAN Journal on Hospitality and Tourism, 2009)
This research analyzes individual's willingness to pay (WTP) for the conservation of Tourism spots in the Damai district, Kuching. Sarawak. The study applied the dichotomaus choice of Contingent Valuation Method (CVM), to visitors sampled randomly. Results indicated a pe,. person median value of RM11. 64 WTP for the preservation of Damai, using the logit modem. The coilection of a fee would allow local authorities to provide and promote various conservation activities, in addition to the reduction of problems associated to the public good.